Prescribing intranasal steroids in HIV-positive patients: systematic review of the literature. Issue 9 (13th September 2021) - Seymour, N; Robinson, M; Richardson, D; Mohammed, H; Williams, D; McGilligan, J A
Abstract: Background: There are significant drug–drug interactions between human immunodeficiency virus antiretroviral therapy and intranasal steroids, leading to high serum concentrations of iatrogenic steroids and subsequently Cushing's syndrome. Method: All articles in the literature on cases of intranasal steroid and antiretroviral therapy interactions were reviewed. Full-length manuscripts were analysed and the relevant data were extracted. Results: A literature search and further cross-referencing yielded a total of seven reports on drug–drug interactions of intranasal corticosteroids and human immunodeficiency virus protease inhibitors, published between 1999 and 2019. Conclusion: The use of potent steroids metabolised via CYP3A4, such as fluticasone and budesonide, are not recommended for patients taking ritonavir or cobicistat. Mometasone should be used cautiously with ritonavir because of pharmacokinetic similarities to fluticasone. There was a delayed onset of symptoms in many cases, most likely due to the relatively lower systemic bioavailability of intranasal fluticasone.